COUPLING OF THE GENERALIZED MULTIPOLE TECHNIQUE AND THE FINITE ELEMENT METHOD - Bomholt, Lars H. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents a coupling of two different methods for electromagnetic scattering problems, the 3D MMP (Multiple MultiPole), code, an implementation of the Generalized Multipole Technique (GMT) and the finite element (FE) method. The coupling is performed using iterative methods. The procedure is illustrated with the solution of a benchmark problem for scattering from a three-dimensional lossy dielectric cylinder. [Vol. 9, No. 3 (1994), Special Issue on Generalized Multipole Technique (GMT), pp 63-68]